Novel Fosfomycin Resistance Mechanism in Pseudomonas entomophila Due to Atypical Pho Regulon Control of GlpT - Laura Sánchez-Maroto; Pablo Gella; Alejandro Couce (Antibiotics)
Background/Objectives: Pseudomonas entomophila is a ubiquitous bacterium capable of killing insects of different orders and has become a model for host–pathogen studies and a promising tool for biological pest control. In the human pathogen Pseudomonas aeruginosa, spontaneous resistance to fosfomycin arises almost exclusively from mutations in the glycerol-3-phosphate transporter (GlpT), the drug’s sole entry route in this species. Here, we investigated whether this specificity is conserved in P. entomophila, as it could provide a valuable marker system for studying mutation rates and spectra and for selection in genetic engineering. Methods: We isolated 16 independent spontaneous fosfomycin-resistant mutants in P. entomophila, and studied the genetic basis of the resistance using a combination of sequencing, phenotyping and computational approaches. Results: We only found two mutants without alterations in glpT or any of its known regulatory elements. Whole-genome sequencing revealed unique inactivating mutations in phoU, a key regulator of the phosphate starvation (Pho) regulon. Computational analyses identified a PhoB binding site in the glpT promoter, and experiments showed that phoU inactivation reduced glpT expression nearly 20-fold. While placing a sugar-phosphate transporter under the Pho regulon may seem advantageous, bioinformatic analysis shows this configuration is atypical among pseudomonads. Conclusions: This atypical Pho regulon control of GlpT probably reflects the peculiarities of P. entomophila’s habitat and lifestyle; highlighting how readily regulatory evolution can lead to the rapid divergence of resistance mechanisms, even among closely related species.